2020
DOI: 10.1108/bepam-01-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of waste diversion rates in the construction and demolition sector in Australia

Abstract: PurposeWaste diversion rate (WDR) is a key indicator of effective waste management and circular economy. However, it has not yet been widely used in the construction and demolition waste (C&DW) sector. This study aims to promote the application of WDR as an effective measure for waste management through the investigation of the current status of C&DW diversion in the Australian construction industry.Design/methodology/approachA mixed-method approach, which combines a desk study and a case study of 12 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…This situation has then pushed manufacturers locally to change their process methods and practices, thus transitioning to a more sustainable approach like circular economy. Furthermore, the principle of circular economy has gained large acceptance in the last few years and has been applied to several industrial sectors like the agri-food sector [23], the mining and extraction sector [24] as well as the construction and demolition sector [25]. The country has also invested in infrastructures and technologies to convert recyclable items like plastics into several other useful products.…”
Section: Circular Economy In Developed Countriesmentioning
confidence: 99%
“…This situation has then pushed manufacturers locally to change their process methods and practices, thus transitioning to a more sustainable approach like circular economy. Furthermore, the principle of circular economy has gained large acceptance in the last few years and has been applied to several industrial sectors like the agri-food sector [23], the mining and extraction sector [24] as well as the construction and demolition sector [25]. The country has also invested in infrastructures and technologies to convert recyclable items like plastics into several other useful products.…”
Section: Circular Economy In Developed Countriesmentioning
confidence: 99%
“…Despite some inconsistencies in waste data among different jurisdictions, these statistics provide an understanding of the Australian C&D waste generation and recycling, encourage public environmental awareness, and support the policy-making of governments. Ratnasabapathy et al (2020) suggested that C&D waste data reporting should be made mandatory, starting from the project level, to assure the reliability and consistency of the national waste data.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…As can be seen from Table 2, they are defined in a general fashion like the United States. This simplicity in definitions at a national level does not correspond to the significance of the CDW material in Australia, as the country generates more than 20 million tons annually [9,78]. 1 for CDW in Australia, China, the European Union, India, the United Nations, and the United States.…”
Section: Legislative Definitions Of Cdw Materialsmentioning
confidence: 99%
“…Therefore, conceptualising the circular economy potential of CDW materials is of great importance for the Australian construction industry as it may help to divert millions of tons of material resources from landfills, which then can be sorted and measured accordingly to support the circular economy indicators. The significance of this concept is underpinned by the high landfilling rate in Australia (27%), which means that approximately 5.5 million tons of material resource potential is wasted annually, threatening the space in the major Australian landfills [9,82].…”
Section: Australiamentioning
confidence: 99%
See 1 more Smart Citation